PEDAGOGICAL PRACTICEAS A MOTIVATOR OF PROFESSIONAL SELF- PERFECTION OF STUDENTS - Sichkar, Alla; Demianenko, Valentina (Educological discourse, 2020)
The article is devoted to the problem of forming motivation for professional self -improvement of students majoring in "Preschool education" in the course of pedagogical practice. According to the study, the article describes different approaches to the problem of development of processes of self-improvement, self-development, self-reflection in scientific works of modern Ukrainian and foreign scientists. It was found that professional self-improvement as an internal process of qualitative self-change is possible, first of all, by teacher’s awareness of the need for self-improvement, formation of internal motivation in self-development and purposeful organized activities aimed at finding opportunities for maximum professional self-realization. The essence and types of motives (pedagogical, personal, social) that encourage students to professional self-improvement are revealed; the necessity of formation an internal motivation for professional growth in future educators of preschool institutions is argued. The influence of pedagogical practice (mandatory component of the educational process of higher education institution) on the formation of professional self-improvement is substantiated; highlighted the tasks, content of educational (psychological and pedagogical) practice of first-year students majoring in "Preschool Education" as the basis of professional self-determination, and features of preparing students for it (master class, self-diagnosis, individual consultations on various practice tasks) on the basis of the Center for Self-Knowledge, which operates at the Pedagogical Institute of Borys Grinchenko Kyiv University. The analysis of empirical research results on the urgency of students' needs for professional self-improvement is carried out, the motives of professional self-improvement are determined; the dynamics of changes in motives that induce first, second and third year students to professional growth are analyzed. The conditions that promote the formation of internal motivation for professional self-improvement of future educators of preschool education institutions during different types of pedagogical practice are outlined; underscored on the inclusion in the content of practices special tasks for the formation of reflection, implementation of information and computer technologies is also needed (electronic portfolio "Personal and professional growth of the student").